Pasteurella multocida meningitis. - Smith, F. R. (BMJ Group, 1980)
Pasteurella multocida appears to be a very rare cause of meningitis. The bacterium has morphological similarities with other causative organisms, particularly Haemophilus influenzae, and its apparent rarity may be due partly to misidentification. This case, only the fourth reported from the United Kingdom, could not be distinuished clinically from the meningitis, owing to other pyogenic bacteria.